A Comrade, A Mother, A Trophy: Women’s Narratives in Soviet Latvian Prose of the 1920s and 1930s - Ļaksa-Timinska, Ilze (Colloquia, 2025)
The article explores the constructed images and narratives of women in Latvian prose written in the USSR during the 1920s and 1930s. It examines how these diaspora texts reflected and negotiated ideological, social, and gender transformations in early Soviet culture. The study asks what kinds of women-centred narratives circulated among Soviet Latvians, how they intersected with questions of identity, belonging, and political loyalty. Methodologically, the article treats narratives as discursive acts that construct meaning and selfhood, combining feminist, imagological, and postcolonial approaches with close textual analysis. The article maps key narrative types to show how literature shaped the image of a “new woman.”